Peningkatan Kompetensi Wirausaha Berbasis E-Commerce Di Kalangan Pelaku Usaha Kelurahan Rumbai - Sonia sischa eka putri; zuhra, Fatimah; Chanra Putra, Ilham (Jurnal Visi Pengabdian Kepada Masyarakat, 2024)
The development of increasingly sophisticated technology means that businesses must develop well and keep up with the times. Competition is not something that is rarely encountered, because with competition, companies can try their best in running their business. Entrepreneurship as an economic driver in implementing Indonesia's development growth is considered capable of reducing the unemployment rate by providing employment opportunities. This condition can be seen from various empirical data which states that the existence of MSMEs is quite dominant in the Indonesian economy with a total of 8.71 million business units in 2022. Community service activities are carried out to provide strengthening business competition for entrepreneurs through e-commerce media in Rumbai Village. The method used in this community service uses the Community Based Research method, which is collaborative research with the aim of being a medium that brings together various related parties for common goals, overcoming and Resolving existing complex problems. Through workshops and training, rattan entrepreneurs in Rumbai Village can increase their understanding of social media as a trading venue that has a good impact on business. The evaluation results showed an increase in participants' understanding of the material taught in the workshop. The participants' response to this activity was very positive, with hopes for the continuation of service activities with in-depth material and further training.